Improving social emotional functioning in adolescents with Developmental Language Disorders: A mini review and recommendations - Arts, Elke; Orobio de Castro, Bram; Luteijn, Ellen; Elsendoorn, Ben; Vissers, Constance T. W. M. (Frontiers in Psychiatry, 2022)
Adolescents with Developmental Language Disorders (DLD) have more difficulties in social-emotional functioning than their typically developing peers (TD), such as shyness and anxiety in social situations, fewer peer relations, greater risk of victimization, social isolation and depression. In addition, they are more likely to report higher levels of hyperactivity and conduct problems. These problems derive from a complex interplay between difficulties in language, social communication, underlying cognitive deficits in Theory of Mind (ToM), Executive Functioning (EF) and self-directed speech (SDS). Aim of this mini review is to provide an overview of studies examining the effectiveness of interventions targeting the factors underlying social-emotional functioning of adolescents with DLD. We found that studies dedicated to social emotional functioning in adolescents with DLD were relatively scarce. Based on this overview, we give suggestions to improve social emotional skills in adolescents with DLD. We propose that intervention programs should target the social, linguistic and cognitive functions underlying social emotional functioning and create opportunities to practise these skills in daily, real-life situations with peers.